Impacts of Voice and Accountability upon Innovation in Pakistan: Evidence from ARDL and Maki Cointegration Approaches. (28th July 2020) - Nadeem, Muhammad Athar; Jiao, Zhilun; Nawaz, Kishwar; Younis, Amna
Abstract : Innovative capacity has a decisive and crucial role in determining who is prospering in the global arena. Innovation is crucial for value creation, high productivity, economic growth, employment, and sustainable development that benefit the consumers, firms, businesses, and economy as a whole. Several institutional, political, and social conditions lead to different responses of innovation. For instance, low voice and accountability may lead to low institutional setting, cronyism, and favoritism in allocation of resources, which can harm innovation. Similarly, the terrorist attack of 9/11 caused horrific scales of destructions, which caught the countries on various fronts such as economic, political, and technological. Further, sound infrastructure and savings rates are essential to enhance innovation. Applying the ARDL approach to cointegration, this study investigates the impact of voice and accountability, terrorism, infrastructure, and savings on innovation in Pakistan. The empirical evidence shows that low voice and accountability and terrorism have adverse impacts on innovation in the short- and long-run periods. Further, findings reveal that inadequate infrastructures and low savings adversely affect the innovation in both periods. Various robust checks such as Maki cointegration, Johansen cointegration test, fully modified ordinary least square, dynamic ordinary least square, and canonical cointegration regression corroborate the results. The findings of the study would be of substantial implications for government and policymakers.